2013
DOI: 10.1124/mol.113.090530
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of Current through Mutated TASK3 Potassium Channels Underlying Birk Barel Syndrome

Abstract: TASK3 (TWIK-related acid-sensitive K 1 channel 3) potassium channels are members of the two-pore-domain potassium channel family. They are responsible for background leak potassium currents found in many cell types. TASK3 channels are genetically imprinted, and a mutation in TASK3 (G236R) is responsible for Birk Barel mental retardation dysmorphism syndrome, a maternally transmitted developmental disorder. This syndrome may arise from a neuronal migration defect during development caused by dysfunctional TASK3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
42
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(45 citation statements)
references
References 51 publications
(67 reference statements)
3
42
0
Order By: Relevance
“…By contrast, FFA has relatively little effect on the related K2P channel TASK3 (Veale et al, 2014). The relative effectiveness of FFA, MFA, and NFA on TREK1 is consistent with that found previously by Takahira et al (2005).…”
Section: Discussionsupporting
confidence: 81%
“…By contrast, FFA has relatively little effect on the related K2P channel TASK3 (Veale et al, 2014). The relative effectiveness of FFA, MFA, and NFA on TREK1 is consistent with that found previously by Takahira et al (2005).…”
Section: Discussionsupporting
confidence: 81%
“…We next considered whether activators of TASK‐2 channels might induce current through T108P mutated channels, as has been seen previously for other non‐functional or reduced‐function, mutated K2P channels (Ma et al , ; Veale et al , ). Changes in external pH are known to regulate TASK‐2 channels (Reyes et al , ).…”
Section: Resultsmentioning
confidence: 99%
“…FFA (100 μM) is a known enhancer of several K2P channels (Veale et al , ; see also Figure ). We showed that this compound is also able to enhance current through both WT TASK‐2 channels (Figure A and B) and TASK‐2_T108C channels (Figure C and D).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…23,45 In this homodimeric conformation the channel is poorly functioning, with low current levels, which are inwardly rectifying and show altered potassium selectivity. 46 When G236 is mutated to an aspartate, however, the current is significantly increased through these channels, remains outwardly rectifying and potassium selective.…”
Section: Discussionmentioning
confidence: 99%